Einleitung zu Arnold Schönbergs Begleitmusik zu einer Lichtspielszene ; Von heute auf morgen - Schönberg, Arnold (Danièle Huillet et Jean-Marie Straub - Volume 1, 2007)
Einleitung zu Arnold Schönbergs Begleitmusik zu einer Lichtspielszene (1972): The major texts, read on-screen (though interrupted at intervals by black frames), are a letter from Schoenberg to Kandinsky explaining his reasons for not participating in the Bauhaus, and a text by Brecht elaborating the relationship between fascism and capitalism. The readings of these texts take up most of the film, which includes Straub and Huillet as on-camera narrators "placing" the texts. The film then concludes with a montage sequence. The political aspect of the film derives not only from the logical argument advanced, the Brecht analysis standing as a critique of Schoenberg's "liberal" position, but also from the film's rejection of documentary norms. At the same time it has been pointed out that Schoenberg's music stands in relation to classical rules of harmonic composition in the same manner that Straub and Huillet films stand in relation to the conventions of dominant cinema. [www.filmreference.com]